Prove that for n > 1n>1 we have 1 xx 3 xx 5 xx 7 xx cdots xx(2n-1) < n^n1×3×5×7××(2n1)<nn?

2 Answers
Sep 9, 2016

See explanation...

Explanation:

If n > 1n>1 is even, then we can consider the terms in pairs from the middle out:

1 xx 3 xx 5 xx 7 xx ... xx (2n - 1)

= 1 xx 3 xx ... xx (n-1) xx (n+1) xx ... xx (2n - 3) xx (2n - 1)

=prod_(k=1)^(n/2) (n-(2k-1))(n+(2k-1))

=prod_(k=1)^(n/2) (n^2-(2k-1)^2)

< prod_(k=1)^(n/2) n^2 = n^n

If n > 1 is odd, then the middle term is n and the other terms can be considered in pairs from the middle out:

1 xx 3 xx 5 xx 7 xx ... xx (2n - 1)

= 1 xx 3 xx ... xx (n-2) xx n xx (n+2) xx ... xx (2n-3) xx (2n - 1)

=n * prod_(k=1)^((n-1)/2) (n-2k)(n+2k)

=n * prod_(k=1)^((n-1)/2) (n^2-4k^2)

< n * prod_(k=1)^((n-1)/2) n^2 = n*n^(n-1) = n^n

Sep 10, 2016

Another approach.

Explanation:

We will be using the assymptotic Stirling inequality formulas
https://en.wikipedia.org/wiki/Stirling%27s_approximation

log_e (n-1)! < n log_e n - n < log_e n!

(log_e (n-1)! < n log_e n - n is true for n ge 8)

or

(n!)/n < n^n e^(-n) < n!

Calling P_(2n-1) = Pi_(k=1)^n(2k-1) we have

P_(2n-1)=((2n)!)/(2^n n!) we have

P_(2n-1) < ((2n)^(2n+1)e^(-2n))/(2^n n^n e^(-n))=2^(n+1)n^(n+1)e^(-n)=(2(2/e)^n n) n^n

Here (2(2/e)^n n) < 1 for n ge 10

so for n ge 10 according to Stirling approximation

P_(2n-1) < n^n